Digital transformation enhances tourism competitiveness, sustainability, and visitor experience in the digital era - Jumhur Hakim; Ida Ayu Ketut Sumawidari; Asma Khan; Basu Dev Lamichhane; Md. Gulam Mokta Dhir; Mutahir Abbas; Nirdosh Agarwal (YAYASAN MITRA PERSADA NUSANTARA, 2026)
This study explores the strategic transformation of the tourism industry in response to the accelerating influence of digital technology. The objective is to analyse how digital tools such as artificial intelligence, big data, social media, and virtual reality are reshaping tourism business models, destination marketing, and customer engagement. By focusing on the integration of technology into tourism management and operations, the research aims to identify strategies that enhance competitiveness, sustainability, and visitor satisfaction. This study adopts a qualitative descriptive method using literature review and document analysis as the primary data sources. Selected studies from peer-reviewed journals, government reports, and industry white papers provide insight into global trends and best practices in digital tourism transformation. The analysis reveals that digital technology facilitates the personalization of travel experiences, streamlines operational efficiency, and broadens market access. In addition, smart tourism initiatives enable real-time interaction and data-driven decision-making, significantly improving destination management and resource sustainability. However, digital transformation also presents challenges, including cybersecurity risks, uneven digital literacy, and the digital divide between regions. In conclusion, successful strategic transformation in tourism requires not only technological investment but also a comprehensive rethinking of organizational culture, human resources, and public-private collaboration. Future policies should emphasize inclusive digital access, innovation-driven development, and adaptive strategies that align with the fast-changing digital landscape.